Changes in Cardiac Function During the Development of Uremic Cardiomyopathy and the Effect of Salvianolic Acid B Administration in a Rat Model - Ma, Danfu; Mandour, Ahmed S.; Elfadadny, Ahmed; Hendawy, Hanan; Yoshida, Tomohiko; El-Husseiny, Hussein M.; Nishifuji, Koji; Takahashi, Ken; Zhou, Zhenlei; Zhao, Yanbing; Tanaka, Ryou (Frontiers in Veterinary Science, 2022)
Background Uremic cardiomyopathy (UC), the main cause of death in progressive chronic kidney disease (CKD), is characterized by diastolic dysfunction. Intraventricular pressure gradients (IVPG) derived from color m-Mode echocardiography (CMME) and two-dimensional speckle tracking echocardiography (2DSTE) were established as novel echocardiographic approaches for non-invasive and repeatable assessment of cardiac function. Previously, salvianolic acid B (Sal B) showed the potential to alleviate concentric LV hypertrophy in the pressure overload model. The purpose of this study was to evaluate the changes in cardiac function in UC and assess the efficacy of Sal B therapy using IVPG and 2DSTE techniques. Materials and methods Twenty-four rats underwent subtotal nephrectomy to produce progressive renal failure and were allocated equally into UC(n=12) and Sal B-UC(n=12) groups and monitored for eight weeks. A sham-operated group was also included in this study (n=12). Sal B was injected from weeks four to eight in the Sal B-UC group. Conventional echocardiography, 2DSTE, and CMME were performed every two weeks post-operation, concomitantly with an evaluation of renal function. Histopathological and immunohistochemistry analyses were carried out to confirm the echocardiography findings. Results Renal failure and myocardial dysfunction were confirmed in the UC group from weeks two through eight. Eccentric and concentric hypertrophy was observed in the UC group, while the Sal B-UC group showed only eccentric hypertrophy. IVPG analysis did not reveal any significant differences between the groups. Edema, inflammation, fibrosis, and immunohistochemical expression of CD3 infiltration were higher in the UC group compared with sham and Sal B-UC groups. Conclusion 2DSTE and IVPG explored the pathophysiology during the development of UC and indicated the incidence of myocardial dysfunction before ventricular morphological changes without intracardiac flow changes. This study confirmed increased ventricular stiffness and fibrosis in UC rats which was potentially treated by Sal B via decreasing edema, inflammation, and fibrosis.